2007
DOI: 10.1002/arch.20185
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic shuttling of the ecdysteroid receptor (EcR) and of ultraspiracle (Usp) from Drosophila melanogaster in mammalian cells: Energy requirement and interaction with exportin

Abstract: The small G protein Ran, which is important for nucleocytoplasmic shuttling of proteins is present, but does not interact with EcR, Usp, and EcR/Usp. As shown by oligomycin treatment, EcR, Usp, and EcR/Usp import is energy dependent. Export of EcR and EcR/Usp is mediated by exportin-1 (CRM-1) as shown by the inhibiting effect of leptomycin B (LMB). Usp remains in the nucleus for more than 24 h. Nuclear retainment of EcR and Usp is energy dependent as shown by treatment with oligomycin. No export signal could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Our previous observations that EcR export is leptomycin B sensitive (Betanska et al, 2007) are confirmed by our present experiments with siRNA targeting exportin1. Similar results have been described for the transport of adenovirus particles (Strunze (Macchi et al, 2004;Miki and Yoneda, 2004) or the NF-kB transcription factor Dorsal, a regulator of dorso-ventral axis formation in early Drosophila embryogenesis, is also known to be a substrate of exportin (Xylourgidis et al, 2006;DeLotto et al, 2007).…”
Section: Role Of Exportin In Nucleocytoplasmic Shuttling Of Ecrsupporting
confidence: 91%
See 2 more Smart Citations
“…Our previous observations that EcR export is leptomycin B sensitive (Betanska et al, 2007) are confirmed by our present experiments with siRNA targeting exportin1. Similar results have been described for the transport of adenovirus particles (Strunze (Macchi et al, 2004;Miki and Yoneda, 2004) or the NF-kB transcription factor Dorsal, a regulator of dorso-ventral axis formation in early Drosophila embryogenesis, is also known to be a substrate of exportin (Xylourgidis et al, 2006;DeLotto et al, 2007).…”
Section: Role Of Exportin In Nucleocytoplasmic Shuttling Of Ecrsupporting
confidence: 91%
“…We demonstrated the presence of Ran in the cell lines of interest (Betanska et al, 2007) but the direct involvement of Ran in nucleocytoplasmic shuttling of the EcR was not demonstrated so far.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this context, it is interesting to note that no export signal could be detected in Usp (Gwóźdź et al, 2007), which is always localized quantitatively in the nucleus (Nieva et al, 2005;Gwóźdź et al, 2007). The export signal present in the ligand binding domain of EcR is unaccessible after heterodimerization with Usp (Betanska et al, 2007) resulting in increased nuclear localization of EcR in the presence of Usp (Nieva et al, 2005), thus allowing an indirect influence of Usp on cell cycle control. Posttranslational modification seems also to be involved.…”
Section: Intracellular Localization Of Ecr Varies During Cell Cyclementioning
confidence: 97%
“…(Lombardi et al, 2008). Intracellular distribution of nuclear receptor is controlled both by import and export (Betanska et al, 2007;Rinnab et al, 2008). In this context, it is interesting to note that no export signal could be detected in Usp (Gwóźdź et al, 2007), which is always localized quantitatively in the nucleus (Nieva et al, 2005;Gwóźdź et al, 2007).…”
Section: Intracellular Localization Of Ecr Varies During Cell Cyclementioning
confidence: 99%